The Formal Establishment of the Book-Selling Business in Peru: The Cases of Juan Jiménez del Río, Pedro Durango de Espinosa, and Andrés de Hornillos (1580-1620) - Cuya Sialer, Alejandra (2018)
There have been booksellers in Peru since 1543. However, it was only after the 1580s that bookselling as a business formalized, increasing these merchants’ presence in the viceroyalty. This process was propelled by various causes. On the one hand, the viceroyalty had been successfully pacified, and had achieved an administrative order and economic position that made the territory attractive for merchants seeking new commercial ventures. On the other, the dispositions of the Council of Trent and the Third Council of Lima obliged the clergy to possess certain texts, creating an important market in need of books. There also already existed educational institutions and personnel in charge of Peru’s colonial administration, which also needed books from Europe of their own. The purpose of this article is therefore to explain the process of formalization of the bookselling business in Peru between 1580 and 1620. To do so, the cases of three Spanish booksellers who were working in Lima at the time have been studied: Juan Jiménez del Río, Pedro Durango de Espinosa and Andrés de Hornillos.